2004
DOI: 10.1176/appi.ajp.161.11.2073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of ECT in Patients With Major Depression and Comorbid Borderline Personality Disorder

Abstract: Patients with borderline personality disorder have a poorer acute response to ECT, but explanations for this finding remain elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 39 publications
4
74
1
4
Order By: Relevance
“…The sample under study has not been evaluated for Axis II disorders, which might have confounded the present results (e.g. Feske et al 2004). Furthermore, a large age range (23-81 yr) of the present sample including elderly patients has to be acknowledged with a significantly better response to ECT in older patients, which is in line with a multi-site longitudinal study (CORE) showing older age to confer a greater likelihood of achieving remission under ECT (O'Connor et al 2001) and another study reporting even the oldest depressed patients to respond to ECT equally well or even better than younger patients (Tew et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The sample under study has not been evaluated for Axis II disorders, which might have confounded the present results (e.g. Feske et al 2004). Furthermore, a large age range (23-81 yr) of the present sample including elderly patients has to be acknowledged with a significantly better response to ECT in older patients, which is in line with a multi-site longitudinal study (CORE) showing older age to confer a greater likelihood of achieving remission under ECT (O'Connor et al 2001) and another study reporting even the oldest depressed patients to respond to ECT equally well or even better than younger patients (Tew et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Untreated comorbid anxiety symptoms might be a predictor of relapses of mood disorders. Comorbidity of personality disorder was also reported to show less response to ECT (42). The results of this study revealed that comorbidity should be kept in mind as a remarkable risk factor for high relapse/recurrence rates.…”
Section: Discussionmentioning
confidence: 56%
“…Bilateral ECT was shown to be more effective than unilateral ECT (22 7 RCT, 1,408 patients) and high dosage procedures are superior than low dosage ones (seven RCT, 342 patients). According to a recent RCT, 87 comorbidity with borderline personality disorder implies less short-term response to the depression symptomatology.…”
Section: Efficacymentioning
confidence: 99%